The AHR represses nucleotide excision repair and apoptosis and contributes to UV-induced skin carcinogenesis. Issue 10 (November 2018) - Pollet, Marius; Shaik, Siraz; Mescher, Melina; Frauenstein, Katrin; Tigges, Julia; Braun, Stephan; Sondenheimer, Kevin; Kaveh, Mana; Bruhs, Anika; Meller, Stephan; Homey, Bernhard; Schwarz, Agatha; et al.
Abstract Ultraviolet B (UVB) radiation induces mutagenic DNA photoproducts, in particular cyclobutane pyrimidine dimers (CPDs), in epidermal keratinocytes (KC). To prevent skin carcinogenesis, these DNA photoproducts must be removed by nucleotide excision repair (NER) or apoptosis. Here we report that the UVB-sensitive transcription factor aryl hydrocarbon receptor (AHR) attenuates the clearance of UVB-induced CPDs in human HaCaT KC and skin from SKH-1 hairless mice. Subsequent RNA interference and inhibitor studies in KC revealed that AHR specifically suppresses global genome but not transcription-coupled NER. In further experiments, we found that the accelerated repair of CPDs in AHR-compromised KC depended on a modulation of the p27 tumor suppressor protein. Accordingly, p27 protein levels were increased in AHR-silenced KC and skin biopsies from AHR−/− mice, and critical for the improvement of NER. Besides increasing NER activity, AHR inhibition was accompanied by an enhanced occurrence of DNA double-strand breaks triggering KC apoptosis at later time points after irradiation. The UVB-activated AHR thus acts as a negative regulator of both early defense systems against carcinogenesis, NER and apoptosis, implying that it exhibits tumorigenic functions in UVB-exposed skin. In fact, AHR−/− mice developed 50% less UVB-induced cutaneous squamous cell carcinomas in a chronic photocarcinogenesis study than their AHR+/+ littermates. Taken together, our data reveal that AHR influences DNA damage-dependent responses in UVB-irradiated KC and critically contributes to skin photocarcinogenesis in mice.